Manhattan For Rent, 1785-1850 - Doucet, Michael J. (Labour / Le Travail, 1991)
The article reviews the book, "Manhattan For Rent 1785-1850," by Elizabeth Blackmar.
Keywords: BLACKMAR; Elizabeth; BOOKS – Reviews; MANHATTAN for Rent 1785-1850 (Book); Nonfiction; REAL property